Minimizing Energy Usage in the Production of Benzene through Hydrodealkylation Toluene Process by Optimizing Heat Transfer Unit in Reactor System - Maulana, Eldino Irfan; Tarikh, Abrarrizal; Widaranti, Ratih Dwi (Journal of Chemical Engineering Research Progress, 2024)
Benzene is a chemical raw material that is widely used without alternatives in the production of high energy solid liquid fuels and polymers. As a result, the global demand of benzene reaches 51 million per year. The process simulator has been utilized to simulate the reactor system of benzene production through the hydrodealkylation of toluene using Peng-Robinson equation-of-state property package. This system is designed to reach 200,000 tons of benzene per year with an optimized heat flow mechanism. By using a heat recovery strategy that utilizes the heat stream outlet from the waste heat boiler (WHB-01) and the partial condenser (PC-01), the net-energy in the simulation has been effectively minimized by saving a total of -23,915,490.40 kJ/h by directing the heat streams to heaters H-01 and H-02, respectively. Considering this strategy, the modified process within the reactor system is conclusively more optimized than the basic process system. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).